Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Sagu Rasa pada Gabungan Kelompok Tani Tagafura di Kelurahan Jaya Kota Tidore Kepulauan - Suwandi Sangadji; Suhardi Suhardi; Cindy Pratiwi M. Ali (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2019)
The large market demand for the processed sago has an economic impact on the Jaya Village. It showed from increasingly amount of demand and decision to buy flavored sago. Higher buying decision on flavored sago was allegedly influenced by the marketing mix factors applied by Tagafura Joint Farmer Groups from Jaya District, Tidore. Therefore, this study aimed to find out the effect of the marketing mix on the purchase decision of flavored sago from Tagafura Joint Farmer Groups. The location of this study was selected purposively, namely in Jaya District, North Tidore, Tidore. This study was conducted from August to December 2018. The primary data in this study was the result of questionnaires that were distributed to 30 respondents chosen using the saturated sample technique. The data was analyzed using tests of validity, reliability, correlation coefficient, determination, simple linear regression, and t-test to test the hypothesis. The results showed that the applied marketing mix factors had a positive and significant effect on the purchase decision of flavored sago from Tagafura Joint Farmer Groups in Jaya, Tidore.